A question of matrices: from the paper questionnaire to web-surveys - Corposanto, Cleto; Molinari, Beba (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2019)
Topics addressed by the authors aim to highlight in what clothes big data present themselves in the eyes of the researcher, tackling the topic since its origins, ie the matrix Variables Cases. In this regard will be taken as an example a number of possible insights on the web ranging from web usage mining, web content mining and web structure mining, not to mention the web survey conveyed through dedicated platforms, Mobile Applications and related secondary data. Those arguments will be addressed through a focus on the extraction of data matrix and the subsequent analysis.